Visualisasi Data Grab Di Daerah DKI Jakarta Menggunakan Aplikasi Tableau - Aryandito Zaidan, Muhammad; Ihsan Ashari, Muhammad (Journal of Information Systems and Business Technology, 2025)
DKI Jakarta, as a center of economic and social activity, has a very high level of community mobility, resulting in various transportation problems, especially traffic congestion. Application-based transportation services such as Grab generate large amounts of travel data that can be used to understand community mobility patterns. This study aims to visualize Grab service data in DKI Jakarta using Tableau to obtain information on activity trends, income, and the most used services in the 2021–2024 period. This study uses a quantitative method with a descriptive analysis approach. Data were collected in the form of a CSV dataset which was then processed through business intelligence stages, including data processing, storage in a database, and visualization in the form of graphs and interactive dashboards using Tableau. The results show that GrabBike, GrabFood, and GrabCar are the most frequently used services, with GrabBike having the highest number of activities and revenues, reaching approximately 7,200 billion rupiah per year. Data visualization in the form of a dashboard is able to present information in a structured, clearer, and easier to understand manner, so that it can be a basis for supporting decision-making for relevant parties in urban transportation management in DKI Jakarta.